2017
DOI: 10.1016/j.ajpath.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

p53 and miR-34a Feedback Promotes Lung Epithelial Injury and Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial lung disease. The pathogenesis of interstitial lung diseases, including its most common form, IPF, remains poorly understood. Alveolar epithelial cell (AEC) apoptosis, proliferation, and accumulation of myofibroblasts and extracellular matrix deposition results in progressive loss of lung function in IPF. We found induction of tumor suppressor protein, p53, and apoptosis with suppression of urokinase-type plasminogen activator (uPA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 63 publications
7
99
0
Order By: Relevance
“…Thus, the present study would provide new findings concerning the relationship between drug-induced EMT and miR-34a in alveolar epithelial cells. On one hand, it has been reported that miR-34a enhanced alveolar epithelial cell apoptosis and promoted BLM-induced pulmonary fibrosis in mice (33). Furthermore, we found that miR-34a mimic introduction increased mRNA expression level of COL1A1 and fibronectin in A549/ABCA3 cells, which are critical extracellular matrix components in pulmonary fibrosis, indicating that miR-34a may contribute to the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, the present study would provide new findings concerning the relationship between drug-induced EMT and miR-34a in alveolar epithelial cells. On one hand, it has been reported that miR-34a enhanced alveolar epithelial cell apoptosis and promoted BLM-induced pulmonary fibrosis in mice (33). Furthermore, we found that miR-34a mimic introduction increased mRNA expression level of COL1A1 and fibronectin in A549/ABCA3 cells, which are critical extracellular matrix components in pulmonary fibrosis, indicating that miR-34a may contribute to the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 51%
“…The tumor suppressor protein p53 induces cell cycle arrest, apoptosis, senescence, and innate immunity. Induction of p53 is associated with lung injury and development of pulmonary fibrosis (33)(34)(35). Type II alveolar epithelial cell (AEC II) apoptosis is associated with acute lung injury and the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Type II alveolar epithelial cell (AEC II) apoptosis is associated with acute lung injury and the development of pulmonary fibrosis. Active induction of p53 and apoptosis are found in AEC II from IPF patients (35). Lung injury due to exposure to DNA-damaging agents like bleomycin rapidly induces p53 expression in AEC II (34).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Increased p53 contributes to AEC apoptosis, which leads to development of PF, and suppression of excessive p53 inhibits AEC apoptosis and prevents PF. 35,41 Chronic lung epithelial injury initiates PF and can be prevented by inhibiting AEC apoptosis through control of excessive p53. 35 However, fLfs populate, continue to expand, and replace epithelial cells in the fibrotic foci of IPF lungs, leading to progressive destruction of lung architecture and loss of lung function.…”
Section: Discussionmentioning
confidence: 99%